1984
DOI: 10.1115/1.3231105
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Flow Vibrations of a Pipe Close to a Rigid Boundary

Abstract: The paper describes the results of a model test series with the purpose of determining the hydroelastic vibrations of a nearbed pipeline span exposed to flow conditions created by steady current, waves and waves superimposed on steady current. The study has been conducted using a model composed of a spring-mounted rigid pipe segment and a flat plate simulating the sea bed. The hydroelastic cross-flow vibrations of the pipe segment are presented as function of the flow velocity, flow condition (waves and/or ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…It has been reported that the maximum response amplitude takes place at the larger reduced velocity V r (V r = U/( f n D), U is the flow velocity, f n is the natural frequency of the cylinder, D is the cylinder diameter) due to the influence of the wall [31,32]. Jacobsen et al [33] studied the amplitude response of a cylinder suspended in a spring system with gap-to-diameter ratios equal to 0, 0.5 and 1. Based on the work by Tsahalis and Jones [31,32] and Jacobsen et al [33], Fredsoe et al [34] investigated the cross-flow vibration of cylinders near a wall, and their study indicated that the transverse vibration frequency is close to the frequency of vortex shedding from a stationary cylinder, when reduced velocity is less than the value of 3 and the initial gap between the cylinder and the wall (e 0 ) is more than 0.3D; For the case of 3 < V r < 8 and 0 < e 0 < 1D the transverse vibrating frequency is noticeably larger than the frequency of vortex shedding from a stationary cylinder.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…It has been reported that the maximum response amplitude takes place at the larger reduced velocity V r (V r = U/( f n D), U is the flow velocity, f n is the natural frequency of the cylinder, D is the cylinder diameter) due to the influence of the wall [31,32]. Jacobsen et al [33] studied the amplitude response of a cylinder suspended in a spring system with gap-to-diameter ratios equal to 0, 0.5 and 1. Based on the work by Tsahalis and Jones [31,32] and Jacobsen et al [33], Fredsoe et al [34] investigated the cross-flow vibration of cylinders near a wall, and their study indicated that the transverse vibration frequency is close to the frequency of vortex shedding from a stationary cylinder, when reduced velocity is less than the value of 3 and the initial gap between the cylinder and the wall (e 0 ) is more than 0.3D; For the case of 3 < V r < 8 and 0 < e 0 < 1D the transverse vibrating frequency is noticeably larger than the frequency of vortex shedding from a stationary cylinder.…”
Section: Introductionmentioning
confidence: 98%
“…Jacobsen et al [33] studied the amplitude response of a cylinder suspended in a spring system with gap-to-diameter ratios equal to 0, 0.5 and 1. Based on the work by Tsahalis and Jones [31,32] and Jacobsen et al [33], Fredsoe et al [34] investigated the cross-flow vibration of cylinders near a wall, and their study indicated that the transverse vibration frequency is close to the frequency of vortex shedding from a stationary cylinder, when reduced velocity is less than the value of 3 and the initial gap between the cylinder and the wall (e 0 ) is more than 0.3D; For the case of 3 < V r < 8 and 0 < e 0 < 1D the transverse vibrating frequency is noticeably larger than the frequency of vortex shedding from a stationary cylinder. Raven and Stuart [36] carried out the full-scale tests upon the vortex-induced vibration of the pipeline, and they indicated that the critical V r number for the occurrence of vibration would be affected by the initial gap.…”
Section: Introductionmentioning
confidence: 99%
“…For the pipeline contact with the bottom, e 0 /D = 0, there is still vibrations occurring on the pipeline, but the critical velocity is large at 0.357. Unlike wall free cylinders, a cylinder in the vicinity of a rigid boundary will not shed regular vortices but still vibrate, as observed by Jacobsen et al (1984). This can be explained by Sumer and Fredsøe (1997) that the vibration of pipeline with small gap ratio are not only caused by the regular vortex shedding, but also to a certain extent self-excited.…”
Section: Viv Of a Pipeline Near An Rigid Seabedmentioning
confidence: 94%
“…VIV of a pipeline, which has been considered as one of the most important reasons for a pipeline failure, may occur when the ocean flow crossing the pipeline is larger than a certain value. Most existing studies on VIV were mainly focused on the vibration amplitude and frequency for a wall-free (Feng, 1968;Sarpkaya, 2004;Govardhan & Williamson, 2006;Vandiver, 2012) or near-bed cylinder (Jacobsen et al, 1984;Yang et al, 2009;Zang & Gao, 2014). However, the critical condition for the onset of VIV is also a crucial parameter in practical engineering, as it is closely related to the allowable length for avoiding VIV of the spanning pipeline.…”
Section: Introductionmentioning
confidence: 99%
“…Jacobsen et al (1984) studied the amplitude response of a cylinder suspended in a spring system near a rigid wall with gap ratios equal to 0, 0.5 and 1. Based on the work by Jacobsen et al (1984), Fredsoe et al (1985) investigated the cross-flow vibration of cylinders near a rigid wall, and their study indicated that the transverse vibration frequency is close to the frequency of vortex shedding from a stationary cylinder, when reduced velocity is less than the value of 3 and the initial gap between the cylinder and the wall (e 0 ) is more than 0.3D. For the case of 3< Vr < 8 and 0< e 0 < 1D the transverse vibrating frequency is noticeably larger than the frequency of vortex shedding from a stationary cylinder.…”
Section: Introductionmentioning
confidence: 99%